The Main Types of Modern Eloquence Are (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Oratory is the art of practical verbal influence, which gives us the opportunity to masterfully use the word as an instrument of thought and persuasion. The goal of rhetoric as a science has become the teaching of free, expedient and convincing speech.